STEM (Science, Technology, Engineering, and Mathematics) Instructional Analysis Towards Learning Competencies Achievement as Reviewed from Vocational Education Students’ Critical Thinking - Wofrid Erlista Bianome; Edy Suprapto; Fahrizal; Basri K; Priyono; Sealtial Mau (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
A proper instructional process is a process that is designed to meet the expected educational goals; hence, an innovative strategy in the learning process is required. One of the instructional models appropriate for use in teaching vocational lesson material is the STEM model. The aim of this study was to analyze the level of usefulness of the STEM model on the learning competencies achievement of vocational students’ in Kupang as reviewed from their critical thinking, with a focus on the materials about automotive engine components maintenance and reparation. The method of this study was a pre-experimental in the form of one group pretest post-test. The subjects studied were twenty-six Light Vehicle Engineering students of Class X Group B of 2022/2023. The data collection techniques used in this study were documentation and 20-question item test sheets implemented in the pre-test and post-test. The data were analyzed with a T-test using SPSS version 29. The descriptive test results showed a significant difference between the means of tests, which was of 23% proving that the STEM model significantly improved students' critical thinking skills. Therefore, it is recommended that the STEM approach be used as an alternative model for teaching engineering subjects.